Development of Seaweed Pudding (Eucheuma spinosum) with Kelakai (Stenochlaena palustris) and Papaya as Snack Alternative for the Prevention of Anemia - Sagita, Anisa; Sefrina, Linda Riski; Elvandari, Milliyantri (Journal Akademik Universitas Swiss German, 2023)
Women of childbearing age are a vulnerable group to anemia so women need high iron intake. The percentage of anemia in women aged 15-24 years in Indonesia is 35,3%. Anemia has a more serious impact on the time of pregnancy, namely the risk of maternal death, premature birth and low birth weight. The purpose of this study was to determine the best formula, analyze the moisture content, ash content, protein, fat, carbohydrates, Iron (Fe) and vitamin C on the development of seaweed pudding (Eucheuma spinosum) with kelakai (Stenochlaena palustris) and papaya as snack alternative for the prevention of anemia. This research is experimental with a Complete Randomized Design consisting of three levels of treatment (seaweed : kelakai : papaya), namely F1 (100:90:210), F2 (125:70:205) and F3 (150:50:200). The results of organoleptic test observations obtained the best formula in formula 3 with the results of the analysis of water content of 95,6%, ash content of 0,49%, protein 0,11%, fat 0,79%, carbohydrates 3,01%, iron 30,6 mg/100 g dry weight and vitamin C 36 mg/ 100 g dry weight. Based on the results and discussion of the research that has been done, seaweed pudding with kale and papaya can be accepted as an alternative food for the prevention of anemia.